Exploring stakeholders' perceived problems associated with the care and support of children and youth with mental ill health in Sweden: a qualitative study - Malin Helander; Mio Fredriksson; Malin Lohela-Karlsson (BMC, 2024)
Abstract Background Care and support for children and youth with mental ill health have become more specialized and are provided by an increasing number of stakeholders. As a result, services are often fragmented, inefficient and unco-ordinated, with negative consequences for the service user and their family. Enhanced collaboration could lead to improved care and support but requires a shared understanding and a joint problem formulation between involved stakeholders to commence. The aim of this study was to explore different stakeholders' perceived problems associated with delivering care and support to children and youth with mental ill health and to discuss how the perceived problems relate to collaboration. Methods A qualitative descriptive study was conducted, using short statements of perceived problems written by stakeholders involved in the care and support of children and youth with mental ill health during an inter-organizational workshop. The 26 stakeholders represented school and student health, primary health care, specialist care, social services, and different service user organizations. Data were collected during February 2020. Inductive content analysis with a summative approach was used when analysing the data. Results The perceived problems were summarized in a model consisting of four main categories: Resources and governance; Collaboration and co-ordination; Knowledge and competence; and Stigma and confidence, containing 24 subcategories. These categories and subcategories were distributed over three levels: Societal level, Organizational level and Individual level. The perceived problems were shared on the category level but to some extent varied between stakeholder groups on the subcategory level. The perceived problems were either directly or indirectly related to collaboration. Conclusions The perceived problems often acted as barriers to achieving successful collaboration. The problems were distributed on all three levels in the developed model, indicating a complex problem. Even though the perceived problems were shared by stakeholders on an overall level, the findings indicate that the stakeholders did not have a completely shared understanding of the perceived problems, as they tended to focus on aspects most relevant to their own organization or perceptions. The challenge is to find which perceived problems are appropriate for inter-organization problem-solving and which can be solved within individual organizations.